Reimagining Cultural Competence: Bringing Buried Dynamics Into the Light. (June 2017) - Foldy, Erica Gabrielle; Buckley, Tamara R.
Many organizations attempt to increase cultural competence as one way to foster organizational change to enhance equity and inclusion. But the literature on cultural competence is largely silent on the role of emotion, despite the strong feelings that inevitably accompany work in cross-racial dyads, groups, and institutions. We offer group relations theory as an approach rooted in the importance of emotions, especially anxiety, and offering a rich awareness of how unconscious processes, including defense mechanisms like splitting and projection, drive that anxiety. We show how this approach helps us both diagnose and address difficult dynamics, including by recognizing entrenched power inequities. We draw on examples from others' research as well as our own research, teaching, and consulting to illustrate key concepts. Ultimately, we argue that buried emotions can create distance and inhibit change. Surfacing and addressing them can foster connection and provide a way for organizations to move forward.